Integration of Tasawuf Ethics in the Islamic Digital Economy: Aqidah, Syari’ah and Akhlaq Framework - Syahlarriyadi; Lutfi; Mujiburrohman (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
The rapid development of the Islamic digital economy has raised significant ethical challenges, particularly in maintaining the integrity of Sharia-based business practices amid technological disruption and globalization. However, existing studies remain limited to discussions on Islamic finance ethics, social finance integration, and digital technology implementation, without offering a holistic ethical framework rooted in Sufi values. The study aims to develop an integrative model that embeds Sufi ethics—such as sincerity (ikhlas), asceticism (Zuhud), and excellence (Ihsan)—within the Islamic digital economy through the framework of Aqidah (faith), Sharia (law), and Akhlaq (ethics). Using a qualitative approach with literature review, the researchers identify the strategic role of Sufi ethics in fostering sustainability, justice, and blessings within digital business practices. The findings reveal that the integration of Sufi ethics strengthens the ethical foundations of Islamic digital enterprises, offering practical solutions to moral dilemmas in the era of digital transformation. This study contributes a novel framework for establishing a spiritually grounded, competitive, and socially impactful Islamic digital economy.